Ijtihad Digital dan Fatwa di Era Artificial Intelligence - Mutia Chairunnisa; Duski Samad; Firdaus ST Mamad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Ijtihad, mufti, and fatwa constitute fundamental elements in the Islamic legal system that ensure the continuity and adaptability of Sharia law across changing times. In the contemporary era, the rapid development of Artificial Intelligence (AI) introduces new dynamics in Islamic legal scholarship, particularly in relation to legal reasoning and fatwa issuance. This study aims to examine the position of ijtihad, mufti, and fatwa in the age of AI and to analyze the extent to which AI can be utilized without replacing the authority of human scholars. The research employs a qualitative approach through library research, drawing on classical and contemporary works of usul al-fiqh, scholarly journal articles, and official documents from religious institutions. The findings indicate that AI lacks essential epistemological and ethical qualities required for ijtihad, such as moral responsibility, intention, and contextual understanding of social realities and maqasid al-shari‘ah. Consequently, AI cannot function as a mujtahid or mufti in determining Islamic legal rulings. Instead, it may serve as a supportive tool to assist scholars in accessing legal sources, conducting textual analysis, and managing religious data more efficiently. The study also identifies key ethical challenges related to authority, accountability, data bias, and contextual sensitivity that must be addressed to ensure responsible use of AI in Islamic law. This research contributes conceptually by clarifying the methodological boundaries of AI in Islamic legal reasoning and emphasizing the continued central role of qualified scholars in fatwa formulation.